Cross-checking OSL ages from different grain sizes to improve chronological reliability in deltaic environments: an example from the Yangtze River Delta - Wang, Xuemei; Nian, Xiaomei; Zhang, Weiguo; Qiu, Fengyue (Frontiers in Marine Science, 2024)
The Yangtze River Delta has experienced intricate sedimentary and environmental changes throughout the Holocene, driven by the interplay of fluvial and marine forcings. This study presents quartz optically stimulated luminescence (OSL) ages and luminescence sensitivity data from a Holocene sediment core MQ, analyzed across four grain-size fractions, ranging from silt to sand. The results reveal substantial variability in OSL ages and sensitivity among grain sizes, with the medium-grain (45–63 μm) fraction yielding the most consistent and reliable results. In contrast, finer and coarser grains tend to overestimate ages due to incomplete bleaching, with the accurate dating of coarser grains requiring more aliquots or single-grain measurements. The variability in luminescence sensitivity reflects changes in sediment provenance and depositional conditions between estuarine and deltaic environments. OSL ages indicate that the sedimentary evolution of the Yangtze River Delta progressed through distinct phases: rapid accumulation during the early Holocene (10–7 ka) driven by rising sea level and valley infilling; reduced sedimentation during the middle Holocene (7–3 ka) related to a dry climate in the catchment; and accelerated deposition in the late Holocene (3 ka–present) associated with enhanced fluvial input linked to intensified human activities. This study highlights the importance of selecting suitable appropriate grain sizes and carefully comparing different fractions in OSL analysis to reconstruct deltaic chronologies accurately. The finding that the medium-grain fraction yields more reliable OSL ages than finer and coarser fractions should be tested in similar settings elsewhere. The results provide valuable insights for future research on complex depositional environments and contribute to a better understanding of long-term environmental changes.